2016
DOI: 10.1038/nn.4266
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical constraints of optogenetic inhibition at presynaptic terminals

Abstract: We investigated the efficacy of optogenetic inhibition at presynaptic terminals using halorhodopsin, archaerhodopsin and chloride-conducting channelrhodopsins. Precisely timed activation of both archaerhodopsin and halorhodpsin at presynaptic terminals attenuated evoked release. However, sustained archaerhodopsin activation was paradoxically associated with increased spontaneous release. Activation of chloride-conducting channelrhodopsins triggered neurotransmitter release upon light onset. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
338
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(357 citation statements)
references
References 27 publications
17
338
2
Order By: Relevance
“…Because neuronal activity is regulated by Na þ and K þ currents under physiological condition, it is expected that KR2 and its variants including KR2 Kþ will show fewer unintentional side effects compared to proton and Cl À pumping rhodopsins. Indeed, it was recently reported that sustained proton pumping activity of AR3 in synaptic terminals induces a pH-dependent Ca 2þ influx that leads to increased spontaneous release of neurotransmitter [68]. The same group also reported that the activation of light-gated Cl À channels triggers neurotransmitter release upon light onset [68].…”
Section: Future Perspectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…Because neuronal activity is regulated by Na þ and K þ currents under physiological condition, it is expected that KR2 and its variants including KR2 Kþ will show fewer unintentional side effects compared to proton and Cl À pumping rhodopsins. Indeed, it was recently reported that sustained proton pumping activity of AR3 in synaptic terminals induces a pH-dependent Ca 2þ influx that leads to increased spontaneous release of neurotransmitter [68]. The same group also reported that the activation of light-gated Cl À channels triggers neurotransmitter release upon light onset [68].…”
Section: Future Perspectivesmentioning
confidence: 97%
“…Indeed, it was recently reported that sustained proton pumping activity of AR3 in synaptic terminals induces a pH-dependent Ca 2þ influx that leads to increased spontaneous release of neurotransmitter [68]. The same group also reported that the activation of light-gated Cl À channels triggers neurotransmitter release upon light onset [68]. Thus, light-driven Na þ and K þ pumps have the potential to become ideal inhibitory tools in some optogenetics experiments.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This approach allowed us to examine how decreased MC activity affects cognition independently of other network reorganizations observed in epilepsy (17). Because ArchT has excitatory effects when illuminated for long periods (18), we switched to halorhodopsin (eNpHR) (fig. S18) for longer MC photoinhibition.…”
mentioning
confidence: 99%
“…Full suppression of spiking in cultured hippocampal neurons expressing Gt ACR2 was achieved at 20-times lower light intensities than that required by the slow ChloC variant, despite the latter being made more light-sensitive at the expense of a dramatically slower kinetics that required extended illumination for full activation (81). Similarly, robust inhibition of action potential firing has been demonstrated in Gt ACR1-expressing neurons (151). However, photoactivation of Gt ACR1 triggered neurotransmitter release and failed to attenuate the evoked response at the presynaptic terminals (151), consistent with the finding that the Cl − concentration maintained in the axon terminals is four to five times higher than that in the parent cell soma.…”
Section: The Known Molecular Functions Of Microbial Rhodopsinsmentioning
confidence: 75%
“…Similarly, robust inhibition of action potential firing has been demonstrated in Gt ACR1-expressing neurons (151). However, photoactivation of Gt ACR1 triggered neurotransmitter release and failed to attenuate the evoked response at the presynaptic terminals (151), consistent with the finding that the Cl − concentration maintained in the axon terminals is four to five times higher than that in the parent cell soma. Therefore, for inhibition of synaptic release ACRs will need to be targeted exclusively to somatodendritic membrane domains.…”
Section: The Known Molecular Functions Of Microbial Rhodopsinsmentioning
confidence: 75%